2001
DOI: 10.2223/jped.237
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neonatal death in Recife: a case-control study

Abstract: Objective: neonatal mortality is the main cause of infant mortality in the city of Recife. The objective of the present study was to determine the major risk factors for neonatal death in Recife in 1995.Methods: this is a case control study. Information was obtained from the mortality and live birth databases after validation of the data set, between January and December 1995. A sample of 456 cases and 2,280 controls was obtained after using the linkage technique between the two data sets. The difference in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
2
2
0
11
Order By: Relevance
“…In the University of Medical Sciences in Iran, it has reported that preterm birth was consistently associated with neonatal mortality. The study conducted in Recife city of Brazil also found out 27 that prematurity was highly associated with neonatal mortality; the study findings were in line to those from our study where preterm birth newborns are more prone to death than full term babies. In the current study, sex of neonate was not a risk factor of neonatal mortality, as similar as the study conducted in Kurdistan province of Iran, 28 but place of delivery (household) which the mentioned previous medical complications and the incidence of PPH among the grand multiparas.…”
Section: Discussionsupporting
confidence: 91%
“…In the University of Medical Sciences in Iran, it has reported that preterm birth was consistently associated with neonatal mortality. The study conducted in Recife city of Brazil also found out 27 that prematurity was highly associated with neonatal mortality; the study findings were in line to those from our study where preterm birth newborns are more prone to death than full term babies. In the current study, sex of neonate was not a risk factor of neonatal mortality, as similar as the study conducted in Kurdistan province of Iran, 28 but place of delivery (household) which the mentioned previous medical complications and the incidence of PPH among the grand multiparas.…”
Section: Discussionsupporting
confidence: 91%
“…In Brazil, some initiatives attempted to evaluate the quality of neonatal intensive care using this methodology. [4][5][6][7] However, the use of individual-based scoring systems for health system evaluations with a large number of health facilities may not be feasible.…”
Section: Neonatal Near Miss Approach In the 2005 Who Global Survey Brmentioning
confidence: 99%
“…Este achado difere do encontrado em Caxias do Sul (6) , possivelmente por serem diferentes amostras, tanto no tamanho como no local onde foi realizado o estudo. Quanto ao relato de óbitos fetais anteriores, houve chance três vezes maior de óbito quando havia relato positivo, confi rmando outros estudos (6)(7)(8) .…”
Section: Métodosunclassified
“…A explicação de menor mortalidade no sexo feminino seria o amadurecimento mais precoce do pulmão fetal no sexo feminino, com diminuição de problemas respiratórios, que estão entre as principais causas de óbito neonatal (6,7) . Em nosso estudo, o sexo feminino aumentou em quase 20% a chance de óbito, mas este dado não foi estatisticamente signifi cativo.…”
Section: Métodosunclassified
See 1 more Smart Citation